New drugs in multiple myeloma – role of carfilzomib and pomalidomide - Jurczyszyn, Artur; Legieć, Wojciech; Helbig, Grzegorz; Hus, Marek; Kyrcz-Krzemień, Sławomira; Skotnicki, Aleksander B. (Contemporary Oncology/Współczesna Onkologia, 2014)
Carfilzomib (CFZ), an epoxyketone with specific chymotrypsin-like activity, is a second-generation proteasome inhibitor with significant activity in patients with relapsed and refractory multiple myeloma. On July 20, 2012, the US Food and Drug Administration approved CFZ to treat patients with multiple myeloma who have received at least two prior therapies including bortezomib (BORT) and an immunomodulatory agent and have demonstrated disease progression on or within 60 days of completion of the last therapy. Cytogenetic abnormalities did not appear to have a significant impact on the CFZ activity. Carfilzomib was well tolerated and demonstrated promising efficacy in patients with renal insufficiency. Pomalidomide (POM) (CC-4047) is a novel immunomodulatory derivative (IMID) with a stronger in vitro anti-myeloma effect compared with “older” IMIDs – thalidomide and lenalidomide (LEN). On February 8, 2013, the US Food and Drug Administration approved POM (Pomalyst, Celgene) for the treatment of MM patients who have received at least two prior therapies including LEN and BORT and have demonstrated progression on or within 60 days of completion of the last therapy. Pomalidomide is a novel IMID with significant anti-myeloma activity and manageable toxicity. This compound has shown high efficacy in MM patients who were resistant to prior use of LEN/BORT as well as in patients with a high-risk cytogenetic profile. Carfilzomib and POM have very high efficacy and will be used also in first line therapy in future.